Employee Engagement Dan Stress Kerja Pengaruhnya Terhadap Kepuasan Kerja Dan Turnover Intention di Aman Villas Nusa Dua – Bali - Wayan Arya Paramarta; Ni Putu Kurnia Darmayanti (Widya Manajemen, 2020)
The aims of this study was to explain the effect of employee engagement and work stress on job satisfaction and turnover intention at Aman Villas Nusa Dua-Bali. The type of data used in this study is qualitative and quantitative data, with data sources namely primary and secondary data. Data collection method is interview, distributing questionnaires to respondents and library research, while the data analysis technique used Smart PLS 3.2.8. The results of this study showed that employee engagement had a positive effect and significant on job satisfaction, work stress had a negative effect but not significant on job satisfaction, employee engagement had a negative effect and significant on turnover intention, work stress had a positive effect and significant on turnover intention, job satisfaction had a negative effect but not significant on turnover intention, employee engagement had a positive effect but not significant on turnover intention trough job satisfaction, work stress had a positive effect but not significant on turnover intention trough job satisfaction at Aman Villas Nusa Dua-Bali.